Photodynamic action of the red laser on Propionibacterium acnes - Rogério Rodrigo Ramos; Jeferson Leandro de Paiva; José Paulo Franco dos Santos Gomes; Nagib Pezati Boer; José Maria Pereira de Godoy; Fernando Batigalia (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Photodynamic therapy is a therapeutic modality that has consolidated its activity in the photooxidation of organic matter, which arises from the activity of reactive oxygen species. Objective: To evaluate the effect of red laser 660nm with the photosensitizer methylene blue on Propionibacterium acnes in vitro. Method: The experimental design was distributed into four groups (1 - control group without the application of light and without photosensitizer, 2 - application of light, 3 - methylene blue without light, and 4 - methylene blue with light). Tests were subjected to red laser irradiation 660nm by four cycles of 5 minutes at 3-minute intervals. Results: It was evidenced the prominence of the fourth cycle (20 minutes) groups 2, 3 and 4. Study limitations: Despite the favorable results, the laser irradiation time photosensitizer associated with methylene blue were not sufficient to to completely inhibit the proliferation of bacteria. Conclusion: Further studies in vitro are recommended to enable the clinical application of this photosensitizer in photodynamic therapy.